No meditation-related changes in the auditory N1 during first-time meditation - Barnes, L.; McArthur, G.; Biedermann, Britta; de Lissa, P.; Polito, V.; Badcock, N. (Elsevier BV, 2018)
Recent studies link meditation expertise with enhanced low-level attention, measured through auditory event-related potentials (ERPs). In this study, we tested the reliability and validity of a recent finding that the N1 ERP in first-time meditators is smaller during meditation than non-meditation – an effect not present in long-term meditators. In the first experiment, we replicated the finding in first-time meditators. In two subsequent experiments, we discovered that this finding was not due to stimulus-related instructions, but was explained by an effect of the order of conditions. Extended exposure to the same tones has been linked with N1 decrement in other studies, and may explain N1 decrement across our two conditions. We give examples of existing meditation and ERP studies that may include similar condition order effects. The role of condition order among first-time meditators in this study indicates the importance of counterbalancing meditation and non-mediation conditions in meditation studies that use event-related potentials.